Studi Pendahuluan: Pembelajaran Berbasis Local Wisdom disertai Strategi Integrated Science untuk Melatihkan Keterampilan Berpikir Kritis IPA Siswa SMP - Wahyuning Putri Lestari (Program Studi Pendidikan IPA FKIP Universitas Jember, 2019)
Education is a process to provide opportunities for students to be able to improve, increase knowledge, skills, attitudes and behavior that are primarily related to critical thinking skills. The success of education can be influenced by several learning factors so that in choosing methods, approaches, models, and strategies, it has an impact on determining the success and failure of a learning. The solution related to the explanation is by using local wisdom-based learning accompanied by an integrated science strategy. This learning emphasizes local wisdom based on learning activities through integrated science strategies. The purpose of this study is to provide alternative solutions related to the learning process to train critical thinking skills of junior high school students. The method used in this study is the study literature on the sharing of related sources. Based on the results of this study is expected to provide a solution to train critical thinking skills of junior high school students. Kata Kunci: local wisdom based learning; integrated science strategies; and students' critical thinking skills